Designing a Community Reporting System for Online Gambling Activities in Aceh - Ardian, Zalfie; Abdullah, Dahlan; Yunizar, Zara; Tarigan, Tasya Amelia; Agil, Helvina (JINAV: Journal of Information and Visualization, 2025)
The rapid proliferation of online gambling in Aceh, despite the formal implementation of Qanun Jinayah as the legal framework for Islamic law, has posed a significant challenge to law enforcement and community governance. One of the most pressing issues is the absence of a secure, anonymous, and accessible reporting mechanism for citizens to report online gambling activities. This study addresses that gap by developing and evaluating a web-based reporting system named SIPELRA (Sistem Pelaporan Rakyat Aceh/Aceh People’s Reporting System). Employing a Research and Development (R&D) approach, the research was conducted through four stages: needs analysis, system design, implementation, and testing. The system was built using the Laravel framework and MySQL database, with strong emphasis on responsive design and data security to ensure user anonymity. Needs analysis revealed that community members prioritize simplicity, anonymity, and reliability in reporting mechanisms. System design was modeled using UML tools, including use case and activity diagrams, while the interface was developed with a minimalistic and culturally contextual design. Testing consisted of blackbox testing to validate functionality and a user satisfaction survey administered to 30 respondents. Results indicated that all core features operated successfully without major errors, and user satisfaction achieved an average score of 4.5 (90%), with data security receiving the highest rating (92%). Case analysis in North Aceh demonstrated diverse gambling practices, including slot-based games and chip trading, with mobile devices as the dominant medium. The findings confirm that SIPELRA is both technically feasible and socially acceptable, offering a strategic innovation for enhancing community participation and strengthening the enforcement of Qanun Jinayah in Aceh